2017
DOI: 10.1097/dcr.0000000000000709
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Experience of Magnetic Anal Sphincter Augmentation in Patients With Fecal Incontinence

Abstract: Magnetic anal sphincter augmentation provided excellent outcomes in patients who retained a functioning device at long-term follow-up. Protocols to reduce early complications will be important to improve overall results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…There were also attempts to treat faecal incontinence surgically by implanting magnetic anal sphincter device [23]. As previously mentioned, D'Addio et al have reported promising results of their current studies on anti-TMEM219 monoclonal antibody (IGFBP3 receptor present in intestinal crypts), both in in vitro and in vivo and in a mouse model [10].…”
Section: Treatmentmentioning
confidence: 79%
“…There were also attempts to treat faecal incontinence surgically by implanting magnetic anal sphincter device [23]. As previously mentioned, D'Addio et al have reported promising results of their current studies on anti-TMEM219 monoclonal antibody (IGFBP3 receptor present in intestinal crypts), both in in vitro and in vivo and in a mouse model [10].…”
Section: Treatmentmentioning
confidence: 79%
“…Pakravan et al 46 reported a success rate of 76% in 18 patients undergoing FENIX implantation, defined as a ≥ 50% reduction in FI rates per week, with no explants. In a longer-term study, Sugrue et al 47 reported on 37 FENIX patients with a median follow-up of 5 years. Therapeutic success rates at 1, 3 and 5 years were 63%, 66% and 53%, respectively.…”
Section: Chapter 4 Discussionmentioning
confidence: 99%
“…62 Other groups found similar success with the magnetic sphincter with comparative results with the artificial bowel sphincter and sacral neuromodulation. [63][64][65][66] In April 2017, the manufacturers (Torax and Ethicon) discontinued sales and studies for the device based on the company's business plans. 67 TOPAS Sling (American Medical Systems)…”
Section: Magnetic Sphincter (Fenix Torax Medical)mentioning
confidence: 99%